Dietary and lifestyle characteristics associated with normal-weight obesity: the National FINRISK 2007 Study. Issue 5 (14th March 2014) - Männistö, Satu; Harald, Kennet; Kontto, Jukka; Lahti-Koski, Marjaana; Kaartinen, Niina E.; Saarni, Suoma E.; Kanerva, Noora; Jousilahti, Pekka
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of the present study was to compare the lifestyle (leisure-time physical activity, smoking habits and alcohol consumption) and dietary (energy-yielding nutrients, dietary fibre and foods) factors of Finns with a new syndrome called normal-weight obesity (NWO) with those of lean and overweight Finns. The representative population-based study included 4786 participants (25–74 years) from the National FINRISK 2007 Study with a health examination and questionnaires. Food intake was assessed using a validated FFQ. NWO was defined to include those with a normal BMI ( < 25 kg/m2) but excessive body fat (for men ≥ 20 % and for women ≥ 30 %) according to WHO definitions. The proportion of participants with a normal BMI was 28 % in men and 42 % in women. Of these, 34 % of the men and 45 % of the women had the NWO syndrome (among all the participants, 10 and 19 %, respectively). The waist circumference of the NWO participants was between that of the lean and overweight participants. Some potential risk factors, such as physical inactivity, (ex)-smoking and alcohol consumption, were related to NWO. In general, the intakes of energy-yielding nutrients were not associated with NWO. Instead, some healthy dietary factors (e.g. low intakes of meat and soft drinks) as well as unhealthy factors (e.g. low intakes of root vegetables, cereals and fish and high intake of confectionery) were related to NWO. The findings might explain why the NWO participants were of normal weight, but had an excessive body fat percentage. In conclusion, the proportion of normal-weight participants with an excessive body fat percentage was surprisingly high. The identification of NWO people may be of importance because although they appear lean, they have some unhealthy lifestyle and dietary habits related to obesity and overall health.